Analisis Kepuasan Pengunjung Terhadap Layanan Perpustakaan Politeknik Negeri Bali - Ni Wayan Dewinta Ayuni; Wayan Hesadijaya Utthavi; AA. Istri Raka Wahyuni (Epigram, 2019)
Library can be said as the heart of the universities. Politeknik Negri Bali (PNB) as one of the universities in Indonesia currently has one library room located on the 2nd floor of the PNB Central Building. Based on the data, the average number of PNB library visitors in the year 2017 is only 15% of the total civitas. This number shows that PNB library has not been optimally utilized. The purpose of this study is to assess the satisfaction of library visitors to PNB library services, so that the PNB library in the future can provide better service and the number of library visitors can increase. The variables used are five service dimensions, namely tangibles, reliability, responsiveness, assurance, and emphaty. The method of analysis used in this study are importance performance analysis (IPA) and analysis of customer satisfaction index (CSI). Results shows that there are some services that need to be maintained, such as the completeness of facilities, updated collection, air circulation, locker safety, convenience in finding references, knowledge of employee, hospitality of employee, concern of employee, response of employee, and good comunication between employee and visitors. According to CSI method, the visitors’ satisfaction level is 76,40% which is classified as satisfied.